CO2 Emission Tracking App for Internal Combustion Engine (ICE) Motorcycle - Lapjaturapit, Kittipon; Pattamanitiworakit , Narawit; Thanhikam, Weerawut (Science, Technology, and Social Sciences Procedia, 2021)
Motorcycle is one of the most widely used transportation in Thailand. Internal Combustion Engine (ICE) is the most common motorcycle type using in Thais daily life. ICE motorcycle is fossil fuel dependence, and one of the most concerned questions about ICE motorcycle is how much CO2 released from it. In this experiment, CO2 emission data is collected from tracking platform. CO2 tracking platform is available on both mobile and web application. CO2 tracking app will calculate emission data from ICE motorcycle by using mathematical models. The model and parameters of CO2 emission will be obtained from the manufacturer’s specification. From this experiment, we obtained CO2 emission data from usage in real situations. Not only the CO2 emission, but also graph of carbon footprint, average CO2 per distance, and overall CO2 emission data are collected. Moreover, we also ranked CO2 emission in experiment, and offer basic reward for that best performance. Best ranking data will be analyzed about driving behavior, route, and model of ICE motorcycle. Analysis of these experimental data could be beneficial to CO2 emission of ICE motorcycle.